(untitled) (Journal of actual problems of jurisprudence, 2018)
On the basis of the President of RK – the Leader of the Nation N.A.Nazarbayev – program documents single questions of jurisprudence in the sphere of regulation of the social and labor relations are considered. Definition of the social and labor relations, and also justification of neсessity of creation of specialized labor courts as the necessary legal tool in achievement of social modernization is given. It is offered to enter in LC of RK the norms limiting abusement of the labor law. Keywords: Modernization, social and labor relations, the collective agreement, interests of workers, social partnership, trade-union institutes.